Fuzzy Gain-scheduling Proportional–integral Control for Improving the Speed Behavior of a Three-phases Induction Motor - Hichem Othmani; D. Mezghani; A. Mami (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
In this article, we have set up a vector control law of induction machine where we tried different type of speed controllers. Our control strategy is of type Field Orientated Control (FOC). In this structure we designed a Fuzzy Gain-Scheduling Proportional–Integral (Pi) controller to obtain best result regarding the speed of induction machine. At the beginning we designed a Pi controller with fixed parameters. We came up to these parameters by identifying the transfer function of this controller to that of Broïda (second order transfer function). Then we designed a fuzzy logic (FL) controller. Based on simulation results, we highlight the performances of each controller. To improve the speed behaviour of the induction machine, we have designend a controller called “Fuzzy Gain-Scheduling Proportional–Integral controller” (FGS-PI controller) which inherited the pros of the aforementioned controllers. The simulation result of this controller will strengthen its performances.